PENERAPAN MODEL SIMPEL KETOS UNTUK MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR PPKN MATERI MEMBANGUN DEMOKRASI INDONESIA BAGI SISWA KELAS XI PERHOTELAN SMK NEGERI 3 PATI - Mukh Nurkamim (Jurnal Pendidikan Ilmu Sosial, 2018)
The purpose of this study is to increase the participation and learning outcomes of PPKn lesson for building Indonesian democracy for 3rd semester hospital department students class XI 2017/2018 academic year in SMK Negeri 3 Pati. This research was carried out through two cycles. in the first cycle, the action taken was the application of a Simple Ketos Learning Model individually and in the second cycle the action taken was the application of a Simple Ketos Learning Model in groups. This research was conducted for 4 months, starting from August 2017 to November 2017. Classroom action research subjects were conducted in 34 of 3rd semester hospital department students class XI 2017/2018 academic year in SMK Negeri 3 Pati. The method and design of the study used the classroom action research method. Data analysis used is descriptive analysis by comparing pre-action values with cycle I and cycle II. The results showed that individual learning participation increased significantly from pre-action 69.75% to 74.92% in the first cycle and increased to 82.92%. In the second cycle and group learning creativity increased from pre-action 69.93% to 75.67 % in cycle I and increased to 84.93% in cycle II. Furthermore, the learning outcomes also increased significantly from pre-action 76% (22 people) passed and the average grade of 76, then became 88% (30 people) passed and the class average 82.2 in the first cycle and increased to 97% (33 people) passed and on average 83 in cycle II. Student participation and learning outcomes about the building Indonesian democracy lesson can be improved through the application of Simple Ketos Learning Model.